2009
DOI: 10.4103/0970-9371.54863
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of Liqui-PREP[TM] cytology system for primary cervical cancer screening in a large urban hospital setting in China

Abstract: Background:Liquid based cytology (LBC) has been reported to increase the sensitivity of cervical cytology, in comparison with conventional cytology Pap smear (CPS). Most LBC systems though require expensive automated devices.Aims:To evaluate the efficiency of a new and inexpensive LBC system - LPT cytology system.Materials and Methods:Cervical screening was performed on 31500 patients utilizing the LPT cytology system test from January 2006 to May 2007. A similar number (n = 31500) of CPS were performed from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 15 publications
(16 reference statements)
1
23
0
Order By: Relevance
“…Similarly both the methods were sensitive to the same extent for inflammation while MLBC is more specific thus agreeing with the findings of (Berstein et al, 2001;Alves et al, 2004) Regarding increase detection rate, our study found high increased detection rate which was consistent with earlier reports (Austin & Ramzy, 1998;Bishop et al, 1998). There was significant difference in concordance rate between CPS & MLBC Thus LBC showed a significantly higher histologically versus cytological concordance referral rate, as also observed by (Deshou et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Similarly both the methods were sensitive to the same extent for inflammation while MLBC is more specific thus agreeing with the findings of (Berstein et al, 2001;Alves et al, 2004) Regarding increase detection rate, our study found high increased detection rate which was consistent with earlier reports (Austin & Ramzy, 1998;Bishop et al, 1998). There was significant difference in concordance rate between CPS & MLBC Thus LBC showed a significantly higher histologically versus cytological concordance referral rate, as also observed by (Deshou et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…Despite its success as a preventive screening tool for cervical cancer, CPS has its limitations (Deshou et al, 2009). False negatives in CPS may be related to inadequate sampling, inadequate transfer of the sample onto the glass slide or deficiencies in the microscopic assessment of the slide (Maksem et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequency of epithelial abnormalities in another study conducted in the United States was reported to be 5.5%, of which 3.3% was AS-CUS, 1.2% was LSIL, 0.3% was HSIL and 0.2% was AGC-NOS [12] . In a study conducted in China, the overall prevalence was 3.12%, on which 2.3% was AS-CUS, 0.41% was LSIL, 0.28% was HSIL, 0.06% was AGC-NOS and SCC was 0.02% [18] . In our study, we detected abnormal smear results to be 5.69%, in which 2.46% was ASC-US, 0.55% was ASC-H, 1.23% was LSIL, 0.78% was HSIL and 0.22% was AGC-NOS.…”
Section: Discussionmentioning
confidence: 99%